Pengembangan PAUD Pro-Lingkungan Hidup Melalui Scalling Dalam Program Integrated Community Development (ICD) PT Tiv. Pandaan di Kabupaten Pasuruan - Fafit Rahmat Aji; Mulyono Wibisono; Rony Rusdiansyah; Yovi Kurniawan (At-Tajdid: Jurnal Ilmu Tarbiyah, 2016)
PT. Tirta Investama-Pandaan Factory (TIV-Pandaan Factory) is one of the companies engaged in bottled water, developing programs Corporate Social Responsibily (CSR) through the empowerment of the people concentrated in the region of the village of Jatianom Karangjati Pandaan District of Pasuruan. The form of empowerment by using an integrated community development (ICD) approach, between economic empowerment, environment, and education. One form of activities in the field of education is the development of environmentally sound early childhood. The result of this activity is developed through programs of early childhood environmental Pro-scaling (Smart School, Care and cultured environment) is already integrated with the Wanjati garbage bank. In its development, early childhood environmental concept located in the hamlet Jatianom Karangjati Pandaan Pasuruan become a pilot early childhood education in the district of Pasuruan